2012
DOI: 10.3109/00365521.2012.725090
|View full text |Cite
|
Sign up to set email alerts
|

Association of TAP1 and TAP2 polymorphisms with the outcome of persistent HBV infection in a northeast Han Chinese population

Abstract: These results suggested that TAP variants were likely to play a substantial role in different outcomes of persistent HBV infection in the studied population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These complexes are trafficked via the trans-Golgi to the plasma membrane, where they are recognized by the T lymphocyte cell receptor (TCR) (13,18). The importance of TAPs and tapasin for expression of HBV CTL epitopes as well as IPR for IFN␥-activated MHC class I-restricted antigen presentation on hepatocytes has been previously reported (11,39), and TAP polymorphism plays a significant role in infection outcomes (59). Particularly, HBV core peptide 18 -27 (FLPSDEFPSV) has been characterized as a CTL epitope (4,5,43,57) with therapeutic potential (8,63).…”
Section: Introductionmentioning
confidence: 99%
“…These complexes are trafficked via the trans-Golgi to the plasma membrane, where they are recognized by the T lymphocyte cell receptor (TCR) (13,18). The importance of TAPs and tapasin for expression of HBV CTL epitopes as well as IPR for IFN␥-activated MHC class I-restricted antigen presentation on hepatocytes has been previously reported (11,39), and TAP polymorphism plays a significant role in infection outcomes (59). Particularly, HBV core peptide 18 -27 (FLPSDEFPSV) has been characterized as a CTL epitope (4,5,43,57) with therapeutic potential (8,63).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently found an association between a TAP1 gene polymorphism with recurrent respiratory papillomatosis 18 . Other studies on polymorphisms in the TAP gene have reported an increased susceptibility to hepatitis B virus (HBV), HIV and human papillomavirus (HPV) infections 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Both TAP 1 and TAP 2 polymorphisms may result in TAP1/2 protein deficiency (reported for rs 1057141, rs 1135216 and rs 241447), which leads to bare lymphocyte syndrome ( 35 ). They were also found to be associated with chronic infections and impaired antigen clearance, which could potentially lead to chronic exposure to potentially harmful substances, and enhance the risk of persistent lung damage ( 36 ). Exposure to inhalation of antigens, as well as their role in IPF pathogenesis, has been widely discussed as an important trigger of lung injury, followed by impaired healing ( 37 ).…”
Section: Discussionmentioning
confidence: 99%